Case Report: Refractory systemic nmastocytosis with AML1::ETO+ acute myeloid leukemia driven by rare KIT mutation: remarkable therapeutic efficacy of avapritinib - Xue, Song; Chen, Man; Sun, Hui-peng; Cao, Xing-yu (Frontiers in Pediatrics, 2025)
This article describes two pediatric SM with AML1::ETO+ AML patients induced by novel KIT exon11 mutations not previously documented in medical literature. Both patients underwent allogeneic hematopoietic stem cell transplantation, but subsequently developed refractory disease progression unresponsive to multiple salvage regiments. Strikingly, avapritinib intervention achieved unprecedented clinical responses in these complex cases.